Imposing a balance of payment constraint on the Kaldorian model of cumulative causation - Arslan Razmi (University of Massachusetts, Department of Economics, 2011)
We combine two strands of Post Keynesian growth theory by imposing a balance of payments constraint on a Kaldorian cumulative causation model. The effects of external and internal shocks, and the degree to which cumulative causation comes into play depends on the exchange rate and capital account regimes. Exports act as the only exogenous drivers of growth only under a regime of fixed exchange rates and in the absence of relative price effects. Under flexible exchange rates, by contrast, it is internal demand that serves as the only exogenous driver of of growth. Moreover, regardless of the type of shock, the presence of cumulative causation does not boost growth, although it may render growth more sustainable.
Keywords: E12; F43; F32; O40; 330; cumulative causation; balance of payments constraint; export-led growth; capital account openness; exchange rate regime